DebaryOmics: an integrative –omics study to understand the halophilic behaviour of Debaryomyces hansenii. Issue 4 (5th November 2021) - Navarrete, Clara; Sánchez, Benjamín J.; Savickas, Simonas; Martínez, José L.
Summary: Debaryomyces hansenii is a non‐conventional yeast considered to be a well‐suited option for a number of different industrial bioprocesses. It exhibits a set of beneficial traits (halotolerant, oleaginous, xerotolerant, inhibitory compounds resistant) which translates to a number of advantages for industrial fermentation setups when compared to traditional hosts. Although D. hansenii has been highly studied during the last three decades, especially in regards to its salt‐tolerant character, the molecular mechanisms underlying this natural tolerance should be further investigated in order to broadly use this yeast in biotechnological processes. In this work, we performed a series of chemostat cultivations in controlled bioreactors where D. hansenii (CBS 767) was grown in the presence of either 1M NaCl or KCl and studied the transcriptomic and (phospho)proteomic profiles. Our results show that sodium and potassium trigger different responses at both expression and regulation of protein activity levels and also complemented previous reports pointing to specific cellular processes as key players in halotolerance, moreover providing novel information about the specific genes involved in each process. The phosphoproteomic analysis, the first of this kind ever reported in D. hansenii, also implicated a novel and yet uncharacterized cation transporter in the response to high sodium concentrations. Abstract : In the present study we have performed an integrated multi‐omics comparative analysis of Debaryomyces hansenii growing at high salt concentrations, using continuous cultivations in controlled lab‐scale bioreactors.